THE METAL BRACKETS STAINLESS STEEL SURFACE ANALYSIS OF THE NICKEL (Ni) AND MANGAN (Mn) ION RELEASE - Grahita Aditya; Arlina Nurhapsari; Balqis Nureska Khomsiana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: The installation of stainless steel metal brackets on the patient's teeth in a long phase will interact with the oral cavity environment which causes the release of ions such as Ni and Mn ions. Their release in the metal bracket can impact the body in the form of hypersensitivity reactions while the impact on the bracket is the bracket surface changes shown by the gap in it. These changes can reduce the effectiveness of orthodontic and aesthetics treatments, quality and the strength of the bracket, and can provide an attachment place for Streptococcus mutans microbe. The aim of this study was to determine the release of the ions (Ni and Mn) on the stainless steel metal bracket surface.Method: This study was a descriptive research. The research sample used a stainless steel metal bracket with 0.22